The uses of journalistic genres in the Algerian print press and its relationship to meeting the gratification of the readership Field study on students of the Institute of Science and Techniques of Physical and Sports Activities - Msila - قعودي, ياسمين إناس; فيروز , عزيز (sports creativity, 2025)
This study aims to find out whether the types of journalism used in the written sports press meet the gratifications of the public by highlighting what is published by sports newspapers, where the descriptive approach was relied upon and as the research community is the students of the Institute of Science and Techniques of Physical and Sports Activities at The University of M’sila, a deliberate sample of 38 students who follow sports newspapers was selected and used the questionnaire as a tool to collect data, The results reached: Sports newspapers have become newsworthy as the use of editorial arts such as the news and the report overwhelmed the rest of the genres such as investigation, column and newspaper articles, which made them unable to meet the wishes of all segments of the sports public, and that the press policy covering sports at the expense of other and dependent on other types of journalism does not contribute to the development of the sports culture of the reader or the level of dialogue and sports discussion.